Evanescent field Mach-Zehnder interferometer sensor for concentration measurement - Ruaa Khalil Musa; Salah Al deen Adnan; Ali Mahdi Hammadi (Journal of Madenat Alelem University College, 2019)
Optical fibers have been widely used in the field of sensing. In this paper, Mach-Zehnder interferometer is designed and constructed for detecting the concentration of solutions based on the excitation of the evanescent wave at the cladding/core interface. Laser diode (LD) with wavelength of 810 nm has been used. 3 cm of cladding has been removed in the middle of 1 m (SMF-28) for the two arms by using hydrofluoric acid (HF). One arm is isolated from the external perturbation, and the other arm is immersed in different concentrations of sucrose solutions range from 10% to 50% and sodium chloride (Nacl) solutions range from 5% to 25%. As the concentration of solution increases the output power decreases and the wavelength shifts toward the red region. The sensitivities of this sensor for different concentration of sucrose solutions and Nacl solutions are 0.017 nm/(% w/v) and 0.0474 nm/(% w/v) , respectively.